Purchasing and the management of materials - Zenz, Gary Joseph (New York : John Wiley and Sons, 1994)
This book is about: The Functions and Contributions of Purchasing anf Materials Management; Purchase Strategy and Forecasting; Basic Procedures and Purchasing Techniques; Organizational Considerations and Alternatives; Sourcing; Quantity and Inventory Planning and Control; Managing Quality; Principles of Price Determination...
Keywords: Management; Industrial procurement -- Management; Materials management